Development of Learning Models in Madrasah in Minority Islamic Area - Haidir Haidir; Joharis Joharis; Salim Salim; Nun Zairina (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This research was conducted in three areas that are included as Muslim minorities in North Sumatra, namely: Kabanjahe, Sidikalang, and Central Tapanuli. This study aims to determine: (1) the learning process that took place in the madrasa before using the group investigation (GI) model. (2) Knowing the learning process in the madrasa after using the group investigation model. (3) Knowing whether there is an increase in student engagement and learning outcomes after using the group investigation model. The results of the application of the group investigation model in learning are known to increase student engagement and overall learning outcomes. This is due to the fact that learning is dominated by student activities (student dominated class). Meanwhile, before the group investigation model was applied, the learning process was dominated by teacher activities (teacher dominated class).